Failure of macrocyclics lactones to control psoroptic mange infection in feedlot and grazing beef cattle - Cantón, Candela (2019)
The current work assessed the relationship between pharmacokinetic behavior andclinical efficacy of ivermectin (IVM) or doramectin (DRM) against natural Psoroptes ovis var. bovis infection in cattle. The study involved two trials (I and II) carried out on different beef cattle production systems, a feedlot (Trial I) and a grazing (Trial II) system.In Trial I, 40 mange-infected steers were allocated into 4 groups (n=10) and treated with a single (day 0) or repeated (days 0 and 7) subcutaneous injection of two different formulations of IVM (1%) at 0.2 mg/kg. In Trial II, 20 grazing calves with active mangeinfection were allocated into 2 groups (n=10) and treated with a single subcutaneous injection of either IVM (1%) or DRM (1%) at 0.2 mg/kg. Blood and skin samples were collected from 8 animals of each group to measure IVM/DRM concentrations by HPLC. Skin scraping samples were collected from each animal and mites were counted. In Trial I,the repeated administration of IVM increasedthe systemic availability and skin drug exposure compared to the single treatment (p<0.05). However, both formulations failed to achieve a clinical mange cure at either single or repeated treatment. Efficacy of IVM was 10% (single dose) and 50% (repeated treatment) at day 14 post-treatment. The noncured animals remained with active mange 28 days post-treatment. No differences (p>0.05)in the P. ovis scores density were observed after single or repeated treatments. In Trial II, there was also a positive correlation betweenIVM or DRM concentrations in plasma and skin samples. Although IVM and DRM failed to obtain a complete parasitological cure, the efficacy of DRM was higher (80%) than those obtained by IVM (10%)(p<0.05).Additional studies are needed to confirm the presence of P. ovis populations resistant to macrocycliclactones, and to enhance the control of psoroptic mange in cattle.